PERAN HUKUM DALAM MENEKAN PRAKTEK PERNIKAHAN DINI SEBAGAI SALAH SATU PENGHAMBAT PERKEMBANGAN EKONOMI - Hadi Nur Ikhwan; Nuzulia Kumala Sari (Jurnal Riset Multidisiplin Edukasi, 2025)
Early marriage is the marriage of a minor. Each country has different age limits for what constitutes a child. According to the United Nations Population Fund (UNFPA), early marriage is a marriage in which both the bride and groom, or one of them, are under 18 years of age. This concept aligns with the Convention on the Rights of the Child, which defines a child as a child if they are under 18. Early marriage occurs in almost every corner of the world, particularly in developing countries. Various backgrounds and reasons underpin early marriage, including ingrained culture, parental mindset, religion, economics, and various other factors. Factors driving the occurrence of unregistered marriages in Indonesia, particularly in developing societies, include the negative perception of spinsterhood if not married after the age of 17, or the practice of marrying between the ages of 14 and 16. Parents hope to receive support from their children after marriage due to limited family finances. Factors influencing the average age of women's first marriage include social, economic, and residential factors (Population and Family Planning Agency, 2012). The research method used in this journal article is normative-juridical. The Policy Research approach, proposed by Ann Majchrzak (1984), defines analyzing emerging social problems so that the findings can be recommended to decision-makers for practical action to resolve them. The research approach is a plan and procedure that defines the steps in data collection, analysis, and interpretation. Law Number 16 of 2019 clearly prohibits underage marriage. Article 1, number 1 of Law Number 23 of 2002 concerning Child Protection, defines a child as a person under 18 (eighteen) years of age, including unborn children. The Constitutional Court of the Republic of Indonesia has issued Constitutional Court Decision Number 22IPUU-XV/2017, one of the considerations of the Constitutional Court in the decision being, "However, when the difference in treatment between men and women impacts or hinders the fulfillment of basic rights or constitutional rights of citizens, whether civil and political rights or economic, educational, social, and cultural rights, which should not be differentiated solely on the basis of gender, then such differentiation clearly constitutes discrimination." The state, through its legal regulations, has attempted to reduce the number of early marriages, but in practice, early marriages are still widely practiced in society, using methods deemed to violate applicable positive law. For example, with the age limit of under 19 (nineteen) years, people resort to the shortcut of unregistered marriages. Therefore, other regulations are still needed so that the law can provide a solution to the prevalence of early marriages, for the benefit of children in organizing their social lives and improving their lives as adults. Early marriage has a serious impact on economic development in society. If this phenomenon... The continued neglect of early marriage in Indonesia has impacted efforts to improve the welfare of the Indonesian people. The impacts of early marriage include low education, low family income, and a consequent decline in human resources.